1975
DOI: 10.1161/01.str.6.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Genesis of Cerebral Vasospasm

Abstract: Experimental Study on the Genesis of Cerebral Vasospasm• The cerebral vasospasm produced by blood, fractions of blood, and blood-borne agents administered intracisternally was studied arteriographically to attain a better understanding of the genesis of vasospasm. The results indicate this phenomenon is multifarious in origin, involving a number of spasmogens. Whole blood, platelets, platelet extracts, some isolated components of platelets, plasma, thrombin, histamine, serotonin and prostaglandins Fi o , E2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(42 citation statements)
references
References 23 publications
(24 reference statements)
1
41
0
Order By: Relevance
“…In 1975, White et al demonstrated that thrombin induced contraction in the canine basilar artery (35). Later, a link between thrombin and cerebral vasospasm in SAH was suggested by both clinical studies with SAH patients and experimental studies with animal models of SAH, as mentioned above (10 -12, 36).…”
Section: Role Of Thrombin and Par 1 In Cerebral Vasospasmmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1975, White et al demonstrated that thrombin induced contraction in the canine basilar artery (35). Later, a link between thrombin and cerebral vasospasm in SAH was suggested by both clinical studies with SAH patients and experimental studies with animal models of SAH, as mentioned above (10 -12, 36).…”
Section: Role Of Thrombin and Par 1 In Cerebral Vasospasmmentioning
confidence: 99%
“…Clot removal, by either surgery (13) or intrathecal application of fibrinolytic agents such as urokinase or tissue plasminogen activator (16 -18), has (10,12,35), plasmin (36), fibrin degradation products (55,56) Platelet-derived substances: serotonin (57,58), thromboxane A2 (25, 59), platelet-derived growth factor (60) Prostaglandins: PGF2α (61, 62), PGE2 (63) Reactive oxygen species and related materials: lipid hydroperoxide (6) Lipid mediators: sphingosine 1-phosphate (64), arachidonic acid (65) Vasoactive substances: endothelin-1 (66,67), angiotensin II (57,58) Increased vascular responsiveness Endothelial damage and dysfunction (3) Increased contractile responsiveness of smooth muscle Increased receptor function: PAR1 (42,43), PDGFR (68) Alteration of signaling proteins: increased activity of Rho kinase (7, 8) Table 2. Current therapeutic strategies for the treatment of cerebral vasospasm…”
Section: Current Strategies For the Treatment Of Cerebral Vasospasmmentioning
confidence: 99%
“…Several putative spasmogens have been shown to be active in the development of cerebral vasospasm (7,15,18,53). It has been established that an inflammatory reaction occurs after SAH (13,57).…”
Section: Discussionmentioning
confidence: 99%
“…erebral vasospasm is the most important cause of morbidity and mortality in patients surviving subarachnoid hemorrhage (SAH), as it can compromise cerebral hemodynamics and lead to the development of delayed ischemic neurological deficits (7,18,53). The mechanism of cerebral vasospasm is still unclear, but is likely to involve a complex chain of events involving inflammatory processes taking place in the arterial wall (6,7,15,18,51).…”
mentioning
confidence: 99%
“…Penfield, in 1932, (quoted by White et al 3 ), showed sensitive aff e rent and eff e re n t motor nerves in the adventitia and in the space between the adventitia and the muscle layer of all cerebral large and small arteries, and vein walls 3 . I n n e rvation of the human carotid vessels is supplied by the sympathetic system, originating mainly f rom the superior cervical ganglion, but also fro m the inferior 4 .…”
mentioning
confidence: 99%